Energy level determination in bulk heterojunction systems using photoemission yield spectroscopy: case of P3HT:PCBM - Grzibovskis, Raitis; Vembris, Aivars (Springer New York LLC, 2018)
Ultraviolet photoelectron spectroscopy (UPS) is commonly used method for energy level determination using planar heterojunction samples in either metal/organic or organic/organic systems. Only some attempts have been made in the study of bulk heterojunction systems. Photoemission yield spectroscopy (PYS) could be applied as a method for organic compound–organic compound interface studies in bulk heterojunction samples. Contrary to the UPS, PYS method does not require ultra-high vacuum, which simplifies experiment setup. Also, scanning depth of PYS is in the range of tens of nanometers, which allows studying deeper layers of the sample instead of only surface layer. In this work, poly(3-hexylthiophene-2,5-diyl) (P3HT) and [6,6]-phenyl C61 butyric acid methyl ester (PCBM) bulk heterojunction thin films were studied as a model system. A mass ratio between P3HT and PCBM in the system was varied from 1:0 to 1:50. Ionization energy dependence on this ratio was studied using two methods: UPS and PYS. To study the influence of the sample morphology on the PYS measurements and obtainable results, phase-separated and homogeneously distributed samples were prepared for analyses. P3HT ionization energy shift of 0.40 eV was observed in the samples made from chloroform solution. Experiments showed the need for a low degree of phase separation between P3HT and PCBM to observe P3HT ionization energy shift using PYS. On the contrary, no ionization energy shift of P3HT was observed in the UPS measurements for the same systems.
Financial support provided by Scientific Research Project for Students and Young Researchers Nr. SJZ2015/20 realized at the Institute of Solid State Physics, University of Latvia, is greatly acknowledged. This work has been supported by the Latvian State Research Program on Multifunctional Materials IMIS2. Jennifer Mann from Physical Electronics is greatly acknowledged for providing UPS data.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; photoemission yield spectroscopy; ultraviolet photoelectron spectroscopy; interface; ionization energy; organic materials; thin films